Pharmacokinetics of Meropenem in Critically Ill Patients with Acute Renal Failure Treated by Continuous Hemodiafiltration - Krueger, W. A. (American Society for Microbiology, 1998)
The pharmacokinetics of meropenem were studied in nine anuric critically ill patients treated by continuous venovenous hemodiafiltration. Peak levels after infusion of 1,000 mg over 30 min amounted to 103.2 ± 45.9 μg/ml, and trough levels at 12 h were 9.6 ± 3.8 μg/ml. A dosage of 1,000 mg of meropenem twice a day provides plasma drug levels covering intermediately susceptible microorganisms. Further reductions of the dosage might be appropriate for highly susceptible bacteria or when renal replacement therapies with lower clearances are applied.